Beyond volume: hospital-based healthcare technology as a predictor of mortality for cardiovascular patients in Korea. Issue 24 (June 2016) - Kim, Jae-Hyun; Lee, Yunhwan; Park, Eun-Cheol
Abstract : Abstract: To examine whether hospital-based healthcare technology is related to 30-day postoperative mortality rates after adjusting for hospital volume of cardiovascular surgical procedures. This study used the National Health Insurance Service–Cohort Sample Database from 2002 to 2013, which was released by the Korean National Health Insurance Service. A total of 11, 109 cardiovascular surgical procedure patients were analyzed. The primary analysis was based on logistic regression models to examine our hypothesis. After adjusting for hospital volume of cardiovascular surgical procedures as well as for all other confounders, the odds ratio (OR) of 30-day mortality in low healthcare technology hospitals was 1.567-times higher (95% confidence interval [CI] = 1.069–2.297) than in those with high healthcare technology. We also found that, overall, cardiovascular surgical patients treated in low healthcare technology hospitals, regardless of the extent of cardiovascular surgical procedures, had the highest 30-day mortality rate. Although the results of our study provide scientific evidence for a hospital volume–mortality relationship in cardiovascular surgical patients, the independent effect of hospital-based healthcare technology is strong, resulting in a lower mortality rate. As hospital characteristics such as clinical pathways and protocols are likely to also play an important role in mortality, further research is required to explore their respective contributions.